2017
DOI: 10.5144/0256-4947.2017.433
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of oral agents in relapsing-remitting multiple sclerosis compared to interferon-based therapy in Saudi Arabia

Abstract: BACKGROUNDPromising clinical and humanistic outcomes are associated with the use of new oral agents in the treatment of relapsing-remitting multiple sclerosis (RRMS). This is the first cost-effectiveness study comparing these medications in Saudi Arabia.OBJECTIVESWe aimed to compare the cost-effectiveness of fingolimod, teriflunomide, dimethyl fumarate, and interferon (IFN)-β1a products (Avonex and Rebif) as first-line therapies in the treatment of patients with RRMS from a Saudi payer perspective.DESIGNCohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…15,16,20,22,23,26,[31][32][33][34]44,49,55,56,62 Thirty seven studies were published in medical journals, [14][15][16][17][18][19][20][22][23][24][25][26][28][29][30][31][32][33]36,38,40,41,44,46,49,50,[52][53][54][55][56][57][58][59][60][61][62] 7 in non-medical journals …”
Section: Publication Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16,20,22,23,26,[31][32][33][34]44,49,55,56,62 Thirty seven studies were published in medical journals, [14][15][16][17][18][19][20][22][23][24][25][26][28][29][30][31][32][33]36,38,40,41,44,46,49,50,[52][53][54][55][56][57][58][59][60][61][62] 7 in non-medical journals …”
Section: Publication Characteristicsmentioning
confidence: 99%
“…The earliest study was published in 1991 14 and the most recent study was published in December 2017. 62 The majority studies were published in 2016 [49][50][51][52][53][54][55][56] ( Figure 2).…”
Section: Publication Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MS prevalence in Saudi Arabia shows that there is increasing in MS rate from 8 to 40 cases per 100.000 of population, this increases may related to well diagnosis and improvement of treatment facilities [13,14]. Furthermore, [3] confirmed that the total number of cases in Saudi Arabia now will be 12,863 per 32 million individuals with mean age of 25 years old which reported by the United Nations, which proves that Saudi Arabia now in the moderate to high risk zone.…”
Section: Significant Of the Studymentioning
confidence: 99%
“…The direct medical costs of MS in the United State are estimated of 10$ billion per year, and the indirect costs remains higher costs through reduced employment or unemployment, need for assistive equipment, paid personal care and productivity loss on later MS progression [2]. According to [3] who reported that in Saud Arabia, each neurology clinic visit for each MS patients coast around 820 Saudi Riyal from the stage of diagnosis to stage of receive require care in the last six years at King Faisal Specialist Hospital & Research Center.…”
Section: Introductionmentioning
confidence: 99%